2010
DOI: 10.1111/j.1528-1167.2010.02669.x
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy surgery in tuberous sclerosis complex: Emphasis on surgical candidate and neuropsychology

Abstract: SUMMARYPurpose: To discuss neuropsychological outcome and candidate of epilepsy surgery for tuberous sclerosis complex (TSC). Methods: To retrospectively analyze clinical data of 25 patients with TSC and epilepsy who underwent epilepsy surgery between 2001 and 2007. Seizure reduction was analyzed at 1-year (1FU), 2-year (2FU), and 5-year (5FU) follow-up visits after surgery, and outcomes of intelligence quotient (IQ) and quality of life (QOL) were evaluated at 2FU. Results: Resective procedures included 14 tub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 30 publications
0
23
0
2
Order By: Relevance
“…We obtained IPD in 20 of the eligible 25 articles (80%) [11], [12], [16][33]. This includes 3 of 8 (38%) articles comprising of 32 participants that we obtained IPD after contacting the corresponding authors.…”
Section: Resultsmentioning
confidence: 99%
“…We obtained IPD in 20 of the eligible 25 articles (80%) [11], [12], [16][33]. This includes 3 of 8 (38%) articles comprising of 32 participants that we obtained IPD after contacting the corresponding authors.…”
Section: Resultsmentioning
confidence: 99%
“…44 A further study of a series of 31 patients evaluated with the Washington Psychosocial Seizure Inventory showed an improvement in psychosocial functioning for those who became seizure free. 45 Liang et al 46 described low IQ as a factor associated with cognitive improvement in a small series of 25 patients with tuberous sclerosis complex (TSC) who underwent epilepsy surgery. Another review paper identified the benefits of epilepsy surgery in 177 patients with tuberous sclerosis, where IQ was reported in 62 cases (50 patients with ID); the authors concluded that deterioration of cognitive functioning may be prevented with epilepsy surgery.…”
Section: Practice Points For Pharmacological Treatments Of Behavioralmentioning
confidence: 99%
“…It is important to look for a seizure focus in cases of tuberous sclerosis or cortical dysplasia, where excision of the lesion or tuber may improve seizure outcome (You et al., 2007; Liang et al., 2010).…”
Section: Treatments For Lgs Based On Clinical Experiencementioning
confidence: 99%